2004
DOI: 10.1103/physrevb.69.155105
|View full text |Cite
|
Sign up to set email alerts
|

Charge and orbital excitations inLi2CuO2

Abstract: We report a resonant inelastic x-ray scattering study of electronic excitations in Li 2 CuO 2 , an insulating compound comprised of ribbons of edge-sharing copper-oxygen chains. Three excitations, which show little dependence on momentum transfer, are observed in our measurements. The lowest-energy excitation at ϳ2.1 eV is dispersionless and is attributed to a localized d-d orbital excitation. We also observe two excitations at ϳ5.4 eV and ϳ7.6 eV which we assign to charge-transfer excitations. These high-ener… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
38
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 35 publications
(40 reference statements)
8
38
0
Order By: Relevance
“…In Li 2 CuO 2 , the situation is more controversial, because in previous experiments with RIXS [22] and other experimental techniques [29][30][31], the ZRS exciton could not be unambiguously observed.…”
mentioning
confidence: 93%
“…In Li 2 CuO 2 , the situation is more controversial, because in previous experiments with RIXS [22] and other experimental techniques [29][30][31], the ZRS exciton could not be unambiguously observed.…”
mentioning
confidence: 93%
“…More recently this technique has been applied to various cuprates including high-T c materials 2,3,4,5,6,7,8,9,10,11 and other highly-correlated electron systems. 12,13,14 A recent RIXS study near the Cu K edge in undoped La 2 CuO 4 (LCO) has revealed three features in its charge excitation spectrum. 5 Two features, labeled A and B, appear at energy transfers ω = 2.2 eV and 3.9 eV, respectively; these features show the largest intensity enhancement at an incident photon energy of E i = 8.991 keV.…”
Section: Introductionmentioning
confidence: 99%
“…4 where the RIXS peak near 2.1 eV has been ascribed to the ZRS using a lowspin GS. Probably, the 2.1 eV-peak should be ascribed to d-d excitations 10,11 . A similar feature has been found in CuGeO 3 (in σ(ω) at lower ω ≈ 1.7 ± 0.1 eV) while the ZRS is clearly observed at 3.4 ± 0.2 eV 17,18 .…”
mentioning
confidence: 99%
“…This will cause a strong T -dependence of various response functions, here presented for the case of the optical conductivity σ(ω). For an illustration of our approach we consider Li 2 CuO 2 being of current interest 1,2,3,4,5,6,7,8,9,10,11,12 , structurally simple, and most importantly, where single crystal data are available in a broad ω-range 1,2 . This system stands for a class of frustrated spin-1/2 chain materials with both small ferromagnetic (FM) NN Cu-Cu exchange coupling J 1 and AFM next-nearest neighbor (NNN) Cu-Cu in-chain exchange J 2 1,3 in terms of a 1D spin-1/2 Heisenberg model…”
mentioning
confidence: 99%